Cho `f(x) = x^4 + ax^3 + bx^2 + cx + d` biết `f(1) = 1 , f(-1) = -3 , f(2) = 3 , f(3) = 5` `.` Tính `f(-2)`

Cho `f(x) = x^4 + ax^3 + bx^2 + cx + d` biết `f(1) = 1 , f(-1) = -3 , f(2) = 3 , f(3) = 5` `.` Tính `f(-2)`

1 bình luận về “Cho `f(x) = x^4 + ax^3 + bx^2 + cx + d` biết `f(1) = 1 , f(-1) = -3 , f(2) = 3 , f(3) = 5` `.` Tính `f(-2)`”

  1. Vì f(1)=1
    → f(1)=1^4+a. 1^3+b. 1^2+c.1+d=1
    → a+b+c+d=0 (1) 
    Vì f(-1)=-3
    → (-1)^4 + a.(-1)^3+b . (-1)^2+c . (-1)+d=-3
    → -a+b-c+d=-4 (2) 
    Vì f(2)=3
    → 2^4+a. 2^3+b .2^2+c.2+d=3 
    → 8a+4b+2c+d=-13 (3)
    Vì f(3)=5
    → 3^4+a . 3^3+b .3^2+c.3+d=5
    → 27a+9b+3c+d=-76 (4)
    Từ (1),(2),(3),(4) ta có:
    $\begin{cases} a+b+c+d=0\\-a+b-c+d=-4\\8a+4b+2c+d=-13\\27a+9b+3c+d=-76\end{cases}$
    ⇔ $\begin{cases} a=-5\\b=5\\c=7\\d=-7 \end{cases}$
    → f(x)=x^4-5x^3+5x^2+7x-7
    → f(-2)=(-2)^4- 5. (-2)^3+5. (-2)^2+7 .(-2)-7
    → f(-2)=55

    Trả lời

Viết một bình luận

Câu hỏi mới